EFEKTIVITAS MODEL PEMBELAJARAN SEJARAH BERBASIS NILAI KEBERAGAMAN PEMUKIMAN ETNIS DI PALEMBANG UNTUK MENINGKATKAN SIKAP TOLERANSI SISWA DI SMA NEGERI 1 MUARA ENIM - Dewi Setyawati; Piki Setri Pernantah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Historical learning based on the important ethnic diversity was applied at schools to improve students’ tolerance. The history of ethnic diversity from the local level is still rarely studied. Students’ tolerance attitude in high school (SMA) is also still low. The reason was in the process of teaching and learning in the classroom, teachers more focused on the cognitive side of students. Students needed a varied learning model to develop an attitude of tolerance. The purpose of this study was to examine the effectiveness of the history learning model of the diversity value from ethnic settlements in Palembang to improve the tolerance attitude of high school students. The application of this learning model using cooperative learning through problem-based learning (PBL) and value clarification technique (VCT). This research Quasi experiment with one control class and one experiment class. This research took sample of tenth grade students (class X) SMA Negeri 1 Muara Enim regency. Based on the result of the statistical test, the average of post-test class was 76,4 and the mean of post-test of control class was 73,7. While the value for the T test obtained 2.423 with a significance level of 0.019 <0.025.